The Hygiene Hypothesis and New Perspectives—Current Challenges Meeting an Old Postulate - Garn, Holger; Potaczek, Daniel Piotr; Pfefferle, Petra Ina (Frontiers in Immunology, 2021)
During its 30 years history, the Hygiene Hypothesis has shown itself to be adaptable whenever it has been challenged by new scientific developments and this is a still a continuously ongoing process. In this regard, the minireview aims to discuss some selected new developments in relation to their impact on further fine-tuning and expansion of the Hygiene Hypothesis. This will include the role of recently discovered classes of innate and adaptive immune cells that challenges the old Th1/Th2 paradigm, the applicability of the Hygiene Hypothesis to newly identified allergy/asthma phenotypes with diverse underlying pathomechanistic endotypes, and the increasing knowledge derived from epigenetic studies that leads to better understanding of mechanisms involved in the translation of environmental impacts on biological systems. Further, we shortly discuss the expansion of the Hygiene Hypothesis to other disease areas like psychiatric disorders and cancer which and conclude that the continuously developing Hygiene Hypothesis may provide a more generalized explanation for health burden in highly industrialized countries also relation to global changes.